Socio-demographic profile of pregnancies and births that occurred in the state of Paraná between 2011 and 2019 (Research, Society and Development, 2021)
This article aims to analyze the socio-demographic profile of pregnancies and births that occurred in the state of Paraná between 2011 and 2019. It is an ecological study that compares social and health indicators of the population of the state. The information came from the Live Births System (SINASC) of the Ministry of Health, from all live births to mothers residing in the state of Paraná, between 2011 and 2019, the last year with available information. Reporting on the social conditions of the locality demonstrates the needs and characteristics of women residents, and contributes to the continuous design of the profile of pregnant women in order to contribute to the construction and evaluation of new health programs for women and children, and targeting of care the needs of the population served. We emphasize that teenage mothers become a vulnerable group, as many have low education followed by school dropouts, and generally belong to social classes with less access to information, so they must receive care that prioritizes their needs.